Sosialisasi Peran Badan Narkotika Nasional Kabupaten Karawang Serta Masyarakat Dalam Upaya Pencegahan Penyalahgunaan Narkotika di Masa Pandemi Covid-19 - Oci Senjaya senjaya; Candra Hayatul Iman; Rina Marlina (Universitas Lancang Kuning, 2021)
The circulation ofnarcotics has actually increased during the Covid-19 pandemic. One of the countermeasures is through integrated Community Service (PkM) activities with Thematic KKN activities. The purpose of implementing this activity is so that the public is aware of several BNNK programs during the pandemic. The method of implementing PkM is carried out with social media facilities, this is used for data search, socialization, outreach to BNNK partners with village / urban village representatives in Karawang Regency, including making applications, Whatsapp groups, social media other, this activity is hoped to be an effort to prevent drug abuse during the Covid-19 pandemic with Whatsapp groups and the media. other social media to exchange information related to efforts to prevent narcotics abuse during the Covid-19 pandemic